Persepsi Guru Terhadap Implementasi Kurikulum Merdeka Belajar di Sekolah Dasar - Sunarni Sunarni; Hari Karyono (Departement of Mathematics Education, 2023)
The purpose of this study was to describe teachers' perceptions of the implementation of the independent curriculum in elementary schools. This research is a qualitative research. Qualitative research is research that explores and understands the meaning of a number of individuals or groups of people originating from social problems. Researchers construct reality and understand its meaning, so this research pays close attention to processes, events, and intensity. Respondents are elementary school teachers. Data collection through interviews. The main instrument of this research is the researcher supported by field notes. All data is collected and analyzed descriptively to obtain reliable and reliable findings. The results of the study show that: (1) the teacher's perception is positive and appreciates the implementation of the Independent Curriculum in elementary schools, (2) the teacher has an important role in the process of developing and implementing the curriculum in elementary schools and success in implementing the curriculum is very dependent on how intense the teacher is in implementing it. curriculum in class; (3) teachers have the ability to develop and apply curricula and design classes, in order to improve the quality of teaching and learning processes; (4) the lack of socialization and specific Bimtek training regarding the formation of Pancasila student profiles; (5) not all teachers in elementary schools apply the Merdeka Curriculum, (6) not all teachers have IT skills, and (7) the constraints in implementing the Independent Curriculum are due to the lack of stability of internet access, especially for remote schools whose geographical location makes it difficult to access the internet.